2023
DOI: 10.1186/s12263-023-00723-4
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of electron transport chain and induction of apoptosis by chrysin nanoparticles targeting succinate-ubiquinone oxidoreductase in pancreatic and lung cancer cells

Abstract: Background Flavonoids may help ameliorate the incidence of the major causes of tumor-related mortality, such as pancreatic ductal adenocarcinoma (PDAC) and lung cancer, which are predicted to steadily increase between 2020 to 2030. Here we compared the effect of chrysin and chrysin nanoparticles (CCNPs) with 5-fluorouracil (5-FLU) on the activity and expression of mitochondrial complex II (CII) to induce apoptosis in pancreatic (PANC-1) and lung (A549) cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Lirdprapamongkol et al found through in vivo and in vitro experiments that chrysin can inhibit breast cancer proliferation under hypoxic conditions and reduce breast cancer lung metastasis [ 44 ]. Also, chrysin could promote apoptosis in lung cancer cells and increase their sensitivity to chemotherapy drugs [ 45 , 46 ]. In this study, we explored the anti-tumor effect of chrysin at the molecular level through in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Lirdprapamongkol et al found through in vivo and in vitro experiments that chrysin can inhibit breast cancer proliferation under hypoxic conditions and reduce breast cancer lung metastasis [ 44 ]. Also, chrysin could promote apoptosis in lung cancer cells and increase their sensitivity to chemotherapy drugs [ 45 , 46 ]. In this study, we explored the anti-tumor effect of chrysin at the molecular level through in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…SDH catalyzes the conversion of succinate to fumarate in the TCA cycle and carries electrons to the respiratory chain's ubiquinone (coenzyme Q) pool. The catalytic subunits in the hydrophilic head of SDH that extend into the mitochondrial matrix are subunits A (SDHA) and B (SDHB) [ 44 ]. These activities are carried out by the membrane-anchoring and ubiquinone-binding SDH subunits, SDHC, and SDHD, respectively as illustrated in (Fig.…”
Section: Succinate-ubiquinone Oxidoreductase (Succinate Dehydrogenase...mentioning
confidence: 99%
“…Lately, there has been a growing interest in the use of natural compounds that can hinder tumor-specific alterations in mitochondrial metabolism. These substances have the potential to serve as an appealing therapeutic approach for triggering the activation of the cellular death process in cancer cells [ 25 , 44 , 49 ]. Flavonoids are commonly found in fruits, vegetables, and a variety of herbal preparations.…”
Section: Succinate-ubiquinone Oxidoreductase (Succinate Dehydrogenase...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, natural substances have attention due to block tumor-specific changes in the mitochondrial metabolism and could be an attractive therapeutic strategy for activating the cell death machinery in cancer cells [47][48][49]. Flavanone group member naringenin (NAR) [2,3-dihydro-5,7-dihydroxy-2-(4hydroxyphenyl)-4H-1-benzopyran-4-one) was discovered by Power and Tutin in 1907 [50].…”
Section: Sdh Target For Anticancer Therapymentioning
confidence: 99%